지상·지중 용기재배가 종가시나무 4년생 묘목의 생장에 미치는 영향 - 진언주; 윤준혁; 배은지; 최수민; 박용배; 최명석; Eon Ju Jin; Jun Hyuck Yoon; Eun Ji Bae; Su Min Choi; Yong Bae Park; Myung Suk Choi (농업생명과학연구, 2015)
본 연구는 조경수의 우량한 묘목 생산과 굴취비용의 절감을 위해 지상․지중 용기재배가 종가시나무 4 년생 묘목의 생장에 미치는 영향을 구명하고자 수행되었다. 플라스틱 용기(상부 Ø19 × 하부 Ø13 × 높이 20㎝)로 묘목을 이식하여 활착시킨 후 묘포에 지중과 지상에 배치하였다. 시험구는 단일용기와 60g 부직포를 혼용한 2가지 처리구로 구분하였으며, A-type(노지묘: 대조구), B-type(지면용기), C-type(지면부직포용기), D-type(지중용기), E-type(지중부직포용기)로 배치하였다. 처리구별 묘목의 상대생장률을 측정한 결과 간장 10.96㎝, 근원경 0.06㎜로 D-type 처리구에서 가장 높은 생장을 보였 다(p<0.05). 건물생산량은 D-type 처리구에서 높게 나타났으며, 묘목 품질지수 또한 D-type 처리구에 서 유의성이 높게 나타나 생장이 가장 우수한 것으로 판단된다(p<0.05). 뿌리형태 특성을 분석한 결과 전체적으로 뿌리길이, 직경, 용적이 D-type 처리구에서 가장 높게 나타났다. 본 실험의 결과를 종합해 볼 때, 지중용기 처리구에서 묘목의 품질이 우수하였으며, 지중용기 재배에 따른 굴취비용 절감이 예상 됨으로 종가시나무 4년생 생산에 적합한 재배방법으로 판단된다. This study was carried out to investigate the effect of the growth and seedling quality index of 4-years old on Quercus glauca Thunb. by both above and below ground container cultivation to produce superior seedlings and in other to cut costs on digging work. The seedling was transplanted plastic containers(top Ø19×bottom Ø13×height 20㎝) and then they were placed on both above and below ground in the nursery. They were arranged with A-type: bare root seedling(control), B-type: container seedling of above ground, C-type: container seedling of above ground with 60g non-woven fabric, D-type: container seedling of below ground and E-type: container seedling of belowground with 60g non-woven fabric. The growth of 4-years old seedling of Q. glauca was significantly the highest in D-type (p<0.05), the height and collar diameter were 10.96cm and 0.14 mm, respectively. The Dry mass production and the seedling quality index were high in D-type(p<0.05), compared with other types. As a result of analyzing root morphological trait, root length, root diameter and root volume, D-type showed the highest tendency. The results of this study indicated that D-type was not only better growth performances but also superior containerized seedlings production. Thus, we are considered D-type is the appropriate way to be good growth and seedling quality and to reduce cost on 4 -years old seedling production of Q. glauca.